2015
DOI: 10.1039/c5ra19272b
|View full text |Cite
|
Sign up to set email alerts
|

45S5 Bioglass analogue reinforced akermanite ceramic favorable for additive manufacturing mechanically strong scaffolds

Abstract: Mechanically strong akermanite-based porous bioceramic scaffolds with appreciable bioactivity and biodegradation were developed via extrusion 3D-printing followed by a low-melt bioactive glass-assisted pressureless sintering process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Particular ions, such as zinc, strontium, magnesium, and manganese, can also be incorporated into the scaffold, adding interesting properties to it and promoting better cell differentiation into osteoblasts [ 146 ]. Bioactive glasses are mainly composed of Na 2 O, CaO, SiO 2 , or P 2 O 5 [ 147 ]. They possess an interesting osteoconductivity and osteoproductivity, favouring progenitor cells’ proliferation and differentiation [ 148 ].…”
Section: Three-dimensional Cell Culture Methodsmentioning
confidence: 99%
“…Particular ions, such as zinc, strontium, magnesium, and manganese, can also be incorporated into the scaffold, adding interesting properties to it and promoting better cell differentiation into osteoblasts [ 146 ]. Bioactive glasses are mainly composed of Na 2 O, CaO, SiO 2 , or P 2 O 5 [ 147 ]. They possess an interesting osteoconductivity and osteoproductivity, favouring progenitor cells’ proliferation and differentiation [ 148 ].…”
Section: Three-dimensional Cell Culture Methodsmentioning
confidence: 99%
“…In general, the main mechanical requirement, however, is the compressive and tensile resistance for the porous cage in the spinal fusion condition. Our previous study (Wang et al, ) have demonstrated that the low‐melt BG could significantly reinforce the AKE (macroporous) bioceramic, and the as‐sintered glass‐ceramics showed appreciable mechanical strength, elastic modulus, and maintained a long‐term mechanical stability in simulated body fluid in vitro. It is reasonable to consider that this mechanical advantage provides a long enough amount of time for the new bone tissue regeneration and ingrowth to form and avoid untimely collapse of the cage.…”
Section: Discussionmentioning
confidence: 97%
“…According to our previous studies (Wang et al, ), the optimized sintering temperature is ~1,050–1,100 °C at which the AKE/BG x produced a high densification without crystal growth. This is evidently helpful for the mechanical improvement at a conventional pressureless sintering condition for the ceramic ink writing bioceramic constructs.…”
Section: Discussionmentioning
confidence: 97%
“…The composites containing 75, 85 and 90% of glass ceramic exhibited very similar compressive strength values. The compressive strength of bioactive glass scaffolds spans from 0.2 to 150 MPa and is composition, microstructure and/or fabrication method dependent, 7,36,37 although macroporous bioactive glass scaffolds can display compressive strength values even below 0.2 MPa. 38 Material crystallinity also plays an important role in mechanical strength and generally increases when the crystalline phase is increased.…”
Section: Mechanical Properties Of Gc-pmma Compositesmentioning
confidence: 99%